Brief Psychological Service Program: A Person-Centered, Person-Empowered Approach to Training and Short-Therapy - Mesa, Maria Lourdes Rosita A (Archīum Ateneo, 2021)
The Brief Psychological Services Program (BPS) was organized to provide psychological support to Filipinos and empower them to effectively cope with the psychological distress during the pandemic. BPS is not an emergency crisis response nor formal mental health treatment, but rather follows a secondary prevention model that aims to address a varied range of distressing reactions and experiences during the pandemic through 1 or 2 sessions. The BPS sessions aim to provide psychological safety, calm, and connectedness within the BPS sessions through establishing therapeutic alliance; and elicit a sense of self-efficacy and hope through the provision of skill-building, problem solving, or perspective-shifting conversations within sessions. The program recruits BPS responders who are graduate-level students in psychology with basic knowledge about counseling and various therapeutic models and techniques and who are likely better equipped to handle a broad range of clients experiencing distress. Some clients who may be identified as requiring severe and urgent care may be referred out for immediate and intensive treatment. The BPS model theorizes a cycle of psychological support and empowerment such that when responders experience these conditions within training, they can provide the same for their clients. Responses of clients’ experiences of BPS will be discussed.